Diversity Analysis of Adult Chironomidae in the Lake Victoria Basin of Kenya - Otieno, Walter Odhiambo; Mosi, Reuben Oyoo; Bulli, Peter (Agricultura Scientia, 2023)
Chironomidae commonly inhabits most aquatic habitats and often dominate aquatic insect communities in abundance and species richness. Despite their ecological importance, the diversity and distribution of chironomids in the Lake Victoria ecosystem of Kenya have not been studied to date. Here we report on the diversity and distribution of adult Chironomidae in Usenge, Mbita and Ogal beaches of the Lake Victoria ecosystem in Kenya using morphological features and sequence data of Cytochrome c oxidase subunit I (COI) gene. Wing venation-based microscopic characterization identified four genera, Tanypus, Coelotanypus, Dicrotendipes and Chironomus. The COI gene barcoding further revealed several species, including Kiefferulus brevibucca, Chironomus flaviplumus, Polypedilum fuscovittatum, Polypedilum sp. and Dicrotendipes sp. The identified species were grouped into three clusters based on neighbor-joining phylogenetic approach. Differences in species richness were observed among the three study sites, with Mbita exhibiting the highest species richness. The evolutionary analysis revealed relatedness among all the identified species, suggesting a shared recent common ancestor. Unlike previous studies, this study represents thefirst report on detailed characterization of Chironomidae in the Lake Victoria ecosystem of Kenya. Moreover, this study serves as a first step towards a comprehensive understanding of the range of species of Chironomidae inhabiting this ecosystem.
Keywords: Chironomidae; cytochrome c oxidase subunit I; DNA barcoding; wing venation; diversity